A gender-focused multilevel analysis of how country, regional and individual level factors relate to harm from others' drinking. (2nd January 2022) - Callinan, Sarah; Karriker-Jaffe, Katherine J.; Roberts, Sarah C. M.; Cook, Won; Kuntsche, Sandra; Grittner, Ulrike; Graham, Kathryn; Room, Robin; Bloomfield, Kim; Greenfield, TomK; Wilsnack, Sharon
Abstract: Background: The aim of this study was to examine how gender, age and education, regional prevalence of male and female risky drinking and country-level economic gender equality are associated with harms from other people's drinking. Methods: 24, 823 adults in 10 countries were surveyed about harms from drinking by people they know and strangers. Country-level economic gender equality and regional prevalence of risky drinking along with age and gender were entered as independent variables into three-level random intercept models predicting alcohol-related harm. Findings: At the individual level, younger respondents were consistently more likely to report harms from others' drinking, while, for women, higher education was associated with lower risk of harms from known drinkers but higher risk of harms from strangers. Regional rate of men's risky drinking was associated with known and stranger harm, while regional-level women's risky drinking was associated with harm from strangers. Gender equality was only associated with harms in models that did not include risky drinking. Conclusions: Youth and regional levels of men's drinking were consistently associated with harm from others attributable to alcohol. Policies that decrease the risky drinking of men would be likely to reduce harms attributable to the drinking of others.